Analisis Proses Rekrutmen, Seleksi, dan Penempatan Kerja Karyawan Outsourcing PT. Nusa Bunga - MARIA HELENA CAROLINDA DUA MEA; FELIXIA IE (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2019)
This study focuses on outsourced employees at PT. Nusa Bunga in the process of recruitment, selection, and work placement. The purpose of this study was to analyze the recruitment, selection and work placement processes carried out by PT. Nusa Bunga to outsourcing employees. The results showed that the responses of outsourcing employees to the recruitment variable if accumulated in its entirety, the number showed the percentage of 82.92%, when viewed from the category of measurement level is ranked 1 (81% -100%) means it is classified as very good. The results showed that the responses of outsourcing employees to the selection also if accumulated in its entirety then the number showed a percentage of 82.4%, when viewed from the category of measurement level was ranked 1 (81% -100%) means it was classified as very good. The results showed that the response of outsourcing employees to work placement if accumulated as a whole then the number showed a percentage of 81.43%, when viewed from the category of measurement level is ranked 1 (81% -100%) means it is classified as very good.